2020
DOI: 10.1039/c9se01095e
|View full text |Cite
|
Sign up to set email alerts
|

Translating local binding energy to a device effective one

Abstract: While nonfullerene acceptors based organic photovoltaics reaching high power conversion efficiency, their binding energy is 150–500 meV. Here there is a model considering disorder and entropy that able to quantitatively explain this controversy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Although we have developed extensive modeling based analysis of solar cells, 12,42 these models contained the hidden assumption that the device structure is a standard one. The energy level diagram, in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have developed extensive modeling based analysis of solar cells, 12,42 these models contained the hidden assumption that the device structure is a standard one. The energy level diagram, in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] It has also been suggested that the inevitable presence of disorder contributes favourably to charge generation. [11][12][13] Understanding the physics of the efficiency of rate of transition from the bound charge transfer (CT) state to free carrier is of immense importance and has been a topic of intensive investigation. [14][15][16] We note that this list nowhere represents the amount of work that has been done in the last 10 years and much can be found in recent reviews.…”
Section: Introductionmentioning
confidence: 99%
“…The Coulomb interaction between an electron and a hole in CTE exceeds dramatically thermal energy at room temperature due to the small intermolecular distance (∼1 nm) and relatively small dielectric constant (ϵr3 ). In this review we do not enter into the discussion about CTE dissociation mechanisms and how the dissociation may be enhanced [35–39] . Importantly CTEs do dissociate to free polarons and contribute to the photocurrent (PC) generated by the OS solar cell.…”
Section: Magnetic Field Effect In Organic Semiconductorsmentioning
confidence: 99%
“…In this review we do not enter into the discussion about CTE dissociation mechanisms and how the dissociation may be enhanced. [35][36][37][38][39] Importantly CTEs do dissociate to free polarons and contribute to the photocurrent (PC) generated by the OS solar cell. Here we focus on the effect of CTE dissociation on the magnetic field response of PC.…”
Section: The Case Of Charge Transfer Excitonmentioning
confidence: 99%
“…The binding energy of the exciton (E b ) influences the optical, electronic, and charge transport properties of the material. [1,2] Therefore, understanding exciton formation, dissociation mechanisms and exciton binding energy, is crucial for unraveling the fundamental photo-physics and enhancing the efficiency of optoelectronic devices, including organic solar cells (OSCs), [3][4][5] and organic photocatalysis for H 2 evolution reaction (HER). [6,7] Excitons can be classified into Frenkel, Wannier-Mott (WM), and chargetransfer (CT) excitons based on their binding energy and degree of delocalization.…”
Section: Introductionmentioning
confidence: 99%